Evaluation of atrial fibrillation (AF) management and cardiovascular risk profile in AF patients: data from Turkish patients in the international observational cross-sectional REALISE AF trial - Erdem Diker; Gokmen Bellur; Nurten Yildiz; Cemil Izgi; Lisa Naditch-brûlé (KARE Publishing, 2015)
Objectives: To assess control of atrial fibrillation (AF) and cardiovascular (CV) risk profile of AF patients with previously established AF therapies. Study design: A total of 510 patients (mean (SD) age, 67.1 (12.3) years, 55.1% females) enrolled from 40 centers across Turkey were evaluated on a single-visit basis in terms of patient demographics, characteristics of underlying AF, the frequency and scoring of symptoms according to European Heart Rhythm Association AF cardiac symptoms classification, control of AF, cardiovascular (CV) risk profile, AF treatment and the consistency of current therapeutic practice with evidence-based guidelines. Results: AF was controlled in 39.4% of patients based on sinus rhythm on the day of visit (10.2%) and AF with HR ≤80 bpm (29.2%). Permanent AF was the most commonly identified type of AF (56.0%). Symptoms were evident in 89.2% of patients either before V0 (78.8%) or at V0 (56.5%). Age (72.4%) and hypertension (70.0%) were the leading CV risk factors. Rate-control and rhythm-control strategies were chosen in 76.5 and 19.2% of patients at the enrollment visit. Mean (SD) of EQ-5D scores for VAS and for single index utility were 63.1 (19.8) and 0.62 (0.4), respectively. Conclusion: In this real life survey of AF patients from Turkey participating in the global contemporary, international, observational, cross-sectional REALISE AF survey, AF was determined to be not optimally controlled, leading patients to experience frequent symptoms, functional impairment and altered QoL,as well as frequent hospital admissions for cardiovascular events and a high requirement for procedures.